Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

Simplify $(-3x^2 y)(5x^4 y^3).$

Simplify 3x2 Y5x4 Y3 class=

Sagot :

Answer: [tex]-15x^6y^4[/tex]

Step-by-step explanation:

(-3x^2 y)(5x^4 y^3)=

-3x^2 *5x^4 *y*y^3=

-3*5*x^2 *x^4 *y^4=

-15*x^(2+4) *y^4=[tex]-15x^6y^4[/tex]

Hope this helped
Check the image below for working
View image Taehyungieee